Reactualization of Islamic Theology: Towards the Transformation of the Islamic Education Paradigm in the Modern Era - Ridwan, Mohammad; Ubaidillah, A; Maryati, Sulis (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
Islamic education has a crucial role in shaping the character and morals of the younger generation, but needs transformation through the reactualization of theology to be relevant to the challenges of modern times. This research uses a qualitative method with library research that examines literature related to Islamic education curriculum, theological values, and technology integration in learning. The findings show that an in-depth evaluation of the existing curriculum is a crucial first step. Curriculum development that combines Islamic theological values with practical learning relevant to modern life is needed. In addition, training and professional development for teachers, as well as the use of educational technology, were identified as important factors in supporting the implementation of the new curriculum. The findings also emphasize the importance of involving the education community, parents and other stakeholders to ensure the success of this transformation. This research shows that the reactualization of theology in Islamic education not only enriches academic content but also shapes learners’ character and morals. The findings have significant implications for policymakers and educational practitioners in designing educational programs that are able to form a generation that is ready to face the challenges of the times by adhering to Islamic values.